Rancang Bangun Role Playing Game Cerita Rakyat Asal Usul Pulomas Berbasis Android - Ayu Latifah; Eri Satria; Alwi Iswahyudi Nugraha (Institut Teknologi Garut, 2022)
Indonesia has a lot of cultures, language and history as well as folklore. Folklore can hone creativity and imagination because folklore contains educational values ​​that can educate morals and character in the younger generation. This research aims to make a Role Playing Game genre game that can introduce folklore, especially on the origins of Pulomas. The story comes from the region of western Java. In this development using the Game Development Life Cycle methodology. The results of this study are in the form of games that utilize the Role Playing game genre in the introduction of folklore which can be accessed using smartphones for teenagers. It is hoped that this game can provide a new experience in introducing folklore to users and can increase user interest in learning folklore in Indonesia.